(untitled) (Fiep Bulletin - online, 2014)
The study proposes to examine the impact of mergers and acquisitions business on ergonomic risks and Musculoskeletal Diseases Repetitive Strain (RSI/WMSD) of workers in operations of Merger and Merger business and the possibilities for the professional practice of physical education . Population comprised 7042 workers, attended by the Reference Center on Health Workers in Greater Recife / PE, between the years 2002-2012. The Brazilian Association of Financial provided data on the operations of Merger and Merger in Brazil. Data were analyzed using the Statistical Package for the Social Sciences version 17. The margin of error was 5.0 % and ranges with 95.0 % reliability. The results showed that ergonomic factors and RSI/WMSD, have a significant association between the workers and predictive business operations of Merger and Merger business. The performance of the professional physical education is significant in the prevention of risks and illnesses.